Collective city making. How commoning practices foster inclusivity. - Köpper, Julia; Müller, Agnes Katharina (My University, 2020)
The article addresses the concept of urban commons, specifically the ways inwhich it can contribute to inclusive urbanism. A container village of about 3,000 m2, the PLATZprojekt is understood as anexperiment in offering people a self-organized space, one they can activelyshape, a space to implement their ideas and to provoke discussion abouttheir city. Initiated by a group of young skateboarders, it was funded by theBBSR (Federal Institute for Research on Building, Urban Affairs and SpatialDevelopment). Situated on a vacant lot in an industrial zone relatively close tothe inner city, the PLATZprojekt seeks to provide space for projects and ideasthat cannot be realised within the gentrified neighbourhoods of dense andcommodified European metropolises.
Keywords: Großstadt; Stadtentwicklungsplanung; Informelle Planung; Gemeinschaftsanlage; Partizipation; Planungsbeteiligung; Inklusion